The 39 steps - Hitchcock, Alfred, 1899-1980.; Bennett, Charles, 1899-1995.; Hay, Ian.; Donat, Robert, 1905-1958.; Carroll, Madeleine, 1906-1987.; Mannheim, Lucie, 1895-1976.; Tearle, Godfrey, 1884-1953.; Ashcroft, Peggy, Dame.; Laurie, John, 1897-1980.; Haye, Helen, 1874-1957.; Cellier, Frank, 1884-1948.; Watson, Wylie; et al. ([New York] : Janus Films, 2006)
Follows the excapades of Richard Hanney, who stumbles into a conspiracy that involves him in a hectic chase across the Scottish moors.
Videodisc release of a 1935 motion picture.
Issued as part of a boxed set of 50 DVDs, with accompanying book: Essential art house : 50 years of Janus Films. Each DVD and the accompanying book are cataloged separately.
Release date: October 24, 2006.
Adapted from the novel by John Buchan.
Photography, Bernard Knowles ; editor, D.N. Twist ; music, Louis Levy.
Robert Donat, Madeleine Carroll, Lucie Mannheim, Godfrey Tearle, Peggy Ashcroft, John Laurie, Helen Haye, Frank Cellier, Wylie Watson.
Keywords: Hannay, Richard (Fictitious character) -- Drama; Intelligence service -- Drama; Detective and mystery films; Feature films